2014
DOI: 10.1016/j.ijgo.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for diagnosis of female genital mutilation

Abstract: Opportunities to identify FGM are frequently missed. Measures should be taken to improve FGM diagnosis and care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
4
36
0
Order By: Relevance
“…Healthcare providers that work with women with FGM in the diaspora or in countries where FGM is ritual can present similarities, such as the difficulty in recognizing and classifying FGM [19], but also differences and specific characteristics to be expressly addressed, such as the problem of medicalization in some African countries or the religious and cultural differences between Western caregivers and migrant patients. The study in Mali in fact, found that, before training, 35 % of the caregivers thought that FGM does not have health risks if performed in a safe environment [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare providers that work with women with FGM in the diaspora or in countries where FGM is ritual can present similarities, such as the difficulty in recognizing and classifying FGM [19], but also differences and specific characteristics to be expressly addressed, such as the problem of medicalization in some African countries or the religious and cultural differences between Western caregivers and migrant patients. The study in Mali in fact, found that, before training, 35 % of the caregivers thought that FGM does not have health risks if performed in a safe environment [11].…”
Section: Discussionmentioning
confidence: 99%
“…The study in Mali in fact, found that, before training, 35 % of the caregivers thought that FGM does not have health risks if performed in a safe environment [11]. Healthcare workers in low prevalence settings may be unfamiliar with cultural issues explaining the persistence of the practice or, could find it difficult or uncomfortable to ask about it because of the fear of embarrassing or causing distress to their patient [19]. …”
Section: Discussionmentioning
confidence: 99%
“…In a study in Eastern Sudan, only 7% of midwives could identify the four types of FGM/C correctly, whereas 81% had practiced the procedure, and in Alexandria, only 7% of nurses could identify the types; in both studies there was little knowledge among these practitioners regarding the medical consequences of the procedure and the majority planned to continue the practice . Similar findings have been reported in diaspora countries; therefore, it behooves ICS members to be aware of the condition and to be prepared to identify and care for these patients . As mentioned above, women who have experienced FGM/C may not know what unaltered anatomy looks like, what type of FGM/C they have personally experienced, and the current symptoms may be so remote from the FGM/C that they do not associate the cause and effect …”
Section: Introductionmentioning
confidence: 66%
“…Despite the fact that WHO has categorized FGM into four types, with some types associated with more adverse complications than others, clinicians, textbook authors, and researchers use these different terms synonymously. This discrepancy can result in substantial (yet preventable) difficulty in the accurate diagnosis and care of patients who have undergone FGM …”
Section: Discussionmentioning
confidence: 99%